Penggunaan Metode Drill untuk Meningkatkan Kemampuan Membaca Tulisan Braille Pada Siswa Tunanetra di SLB-A Bartemeus Manado - Masje Fin Takaredas (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to improve the ability to read Braile writing by using the Drill method assisted by Braille reading board media. The process of applying the method can motivate blind students to be happy and like learning in learning to read the letters AZ, create and read words, read short sentences and read long sentences using Braille reading boards. This research uses Classroom Action Research (CAR), with 3 cycles. The results showed that there was an increase or progress in the interest in learning to read in class II blind students of SLB A Bartemeus Manado. This is known from the results of the analysis of the first cycle of 50%, the second cycle shows an increase of 70% and the third cycle shows a significant increase of 90%. The atmosphere of learning activities shows that the active interaction of students and teachers is able to create an effective learning activity process, especially by using media that is in accordance with the objectives of learning activities